2007
DOI: 10.1021/tx7003618
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Glyceraldehyde 3-Phosphate Dehydrogenase Sulfhydryl Groups with Bis-Electrophiles Produce DNA–Protein Cross-Links but Not Mutations

Abstract: The environmental contaminant 1,2-dibromoethane and diepoxybutane, an oxidation product of the important industrial chemical butadiene, are bis-functional electrophiles and known to be mutagenic and carcinogenic. One mechanism by which bis-electrophiles can exert their toxic effects is through the induction of genotoxic and mutagenic DNA-peptide crosslinks. This mechanism has been shown in systems overexpressing the DNA repair protein O 6 -alkylguanine DNA-alkyltransferase (AGT) or glutathione S-transferase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…replication, transcription, and recombination. 37 DNA-protein cross-links induced by DEB were first observed in livers of B6C3F1 mice exposure to BD 38 and have been reported in vitro including O 6 -alkylguanine DNA alkyltransferase (AGT), 49 glyceradehyde 3-phosphate dehydrogenase, 40 and histone H3. 41 However, there is no evidence that DEB-derived DNA-protein cross-links generate mutations, aside from the case of these formed with AGT.…”
Section: Discussionmentioning
confidence: 99%
“…replication, transcription, and recombination. 37 DNA-protein cross-links induced by DEB were first observed in livers of B6C3F1 mice exposure to BD 38 and have been reported in vitro including O 6 -alkylguanine DNA alkyltransferase (AGT), 49 glyceradehyde 3-phosphate dehydrogenase, 40 and histone H3. 41 However, there is no evidence that DEB-derived DNA-protein cross-links generate mutations, aside from the case of these formed with AGT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main GAPDH function is not related with DNA recognition, this enzyme was shown to interact with various DNA damages including structural analogues of nucleotides used for anticancer therapy, such as thioguanine, mercaptopurine, cytosine arabinoside and 5-fluorouracil [28,29]; covalent DNA adducts with the alkylating agents saframycin [30] and S23906-1 (benzoacronicine derivative) [31]; covalent DNA adducts with bis-electrophiles, e.g. 1,2-dibromoethane and diepoxybutane [53] that allows to propose the involvement of GAPDH in DNA repair. In addition, direct interaction of GAPDH with some proteins participating in DNA repair has been reported [32,29].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 DNA-protein cross-links induced by DEB were first reported in liver tissue of B6C3F1 mice exposure to butadiene. 41 Recently, cross-linking studies induced by DEB with purified recombinant proteins have been reported in vitro including O 6 -alkylguanine DNA alkyltransferase (AGT), 42 glyceradehyde 3-phosphate dehydrogenase (GAPDH), 43 and histone H3. 44 Although GAPDH and histone H3 with DEB form DNA-protein cross-links, the adducts are not mutagenic.…”
Section: Discussionmentioning
confidence: 99%